Laryngeal Osteochondromatosis, A Rare and Potentially Fatal Diagnosis - Manal, Rhezzali; enourhbi, Abdellah; Ennour idrissi, Ilyass; Abou Elhassan , Taoufik; Hicham, Nejmi (International Journal of Innovative Research in Medical Science, 2024)
Osteochondromas are relatively common benign bone tumors often located at the metaphyseal ends of long bones, however, they are very rare in the head and neck region. we present a case of 41 years old, old man with osteochondromatasis of the laryngeal, tracheal and bronchial cartilage hospitalized in intensive care for respiratory distress.